Synthesis, Processing, Structure and Properties of Polymer Materials - Puszka, Andrzej; Podkościelna, Beata (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The aim of this reprint is to highlight the progress and fundamental aspects for the synthesis, characterization, properties, and application of novel polymeric materials, as well as their copolymers, composites, and nanocomposites.